If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(6x-5)(-4x+5)=0
We multiply parentheses ..
(-24x^2+30x+20x-25)=0
We get rid of parentheses
-24x^2+30x+20x-25=0
We add all the numbers together, and all the variables
-24x^2+50x-25=0
a = -24; b = 50; c = -25;
Δ = b2-4ac
Δ = 502-4·(-24)·(-25)
Δ = 100
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{100}=10$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(50)-10}{2*-24}=\frac{-60}{-48} =1+1/4 $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(50)+10}{2*-24}=\frac{-40}{-48} =5/6 $
| 4x^2-3x+14=0 | | 8x+x^2=90 | | 7(2x+4)=x(5+10) | | -(3-2x)=-7+4x | | -8−3d=-2d−2 | | 3/4w=3/8 | | 24=4p | | 3x+x/2=182 | | 2n+5+n+3n=3 | | (5x+4=) | | -11x^2+13x=0 | | 26=9x+11 | | -6(x-13=-54 | | -11^2+13x=0 | | -4(x-11=-44 | | -5p+6=-9−p−9 | | 189x+10=99 | | (5x-10)(3x+9)=0 | | -8s+9=-7s | | (1/3)^6-x=81 | | -2-3k-2=-2k+8-k= | | -4a-7-5a=10+a | | 5x+3=2x−6 | | -8+6h=7h−3 | | 16n+10=5n | | 7q+3=5q-4 | | 1+2t=t+10 | | 3+2t-2=6t+3-2t | | 2/7(x+13)=8 | | 2(x+4)3=12 | | 2*81^(-x)=5*9^(-x)+3 | | 26=7x+11 |